2013
DOI: 10.1051/alr/2013050
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic rate of blue mussels (Mytilus edulis) under varying post-harvest holding conditions

Abstract: The mussel (Mytilus edulis) is successfully grown in aquaculture in Europe. Mussels are usually sold live and wet storage is becoming more common. In this study, oxygen demand and ammonia excretion were assessed at increasing water temperatures and different post-harvest situations. This information was used to calculate minimal flow rates per unit biomass of live mussels sufficient to keep oxygen above 5 mg L −1 or 50% saturation, and avoid accumulation of ammonia in commercial wet storage. In this study, rop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 36 publications
2
13
0
1
Order By: Relevance
“…The duration of exposure to ammonia was 96 hours and observation recorded hourly. Cockles were not fed during the observation to reduce ammonia production/interference [23]. The death of the cockles was confirmed by its inability to close the valves upon mechanical stimulus such as touching it with glass rod [24] and immediately removed from the container.…”
Section: Methodsmentioning
confidence: 99%
“…The duration of exposure to ammonia was 96 hours and observation recorded hourly. Cockles were not fed during the observation to reduce ammonia production/interference [23]. The death of the cockles was confirmed by its inability to close the valves upon mechanical stimulus such as touching it with glass rod [24] and immediately removed from the container.…”
Section: Methodsmentioning
confidence: 99%
“…Aquatic products are not an exception, but even more restricted regarding freshness. Living preservation and transportation have become hot spots of investigation to increase the quality and value of the aquatic product supply chain (Anacleto, et al, 2013;Barrento, Lupatsch, Keay, & Christophersen, 2013;Barrento, Marques, Pedro, Vaz-Pires, & Nunes, 2008;Fotedar & Evans, 2011). Transportation and preservation of live aquatic animals in waterless conditions were developed Cho, Kim, Lee, & Choi, A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 6 technology.…”
Section: Introductionmentioning
confidence: 99%
“…Transportation and preservation of live aquatic animals in waterless conditions were developed Cho, Kim, Lee, & Choi, A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 6 technology. Conventional optimizing methods, based on limited information revealed by physiology indexes (Anacleto, et al, 2013;Barrento, et al, 2013;Barrento, et al, 2008;Fotedar, et al, 2011;Funatsu, Kawasaki, Usui, Nakategawa, Shimizu, & Abe, 2007), are usually superficial and aimless. We utilized a metabolomics approach to establish practical guidance for optimization of preservation and transportation parameters and discover the mechanisms of the stresses the scallops suffered.…”
Section: Introductionmentioning
confidence: 99%
“…Different numbers denote statistical significance at least P b 0.05%, inside discrete supply chain stage. strategy, which we have termed "overpacking" (Barrento et al, 2013b). Overall, in this study, depurated mussels lost less weight during transport (3%) than the numbers reported by mussel farmers (8%).…”
Section: Discussionmentioning
confidence: 56%
“…fresh smell). To improve the industry it is essential to understand the ecology and physiology of M. edulis and relate it to commercial practices and economic demand particularly for the rope grown mussel sub-sector (Barrento et al, 2013a(Barrento et al, , 2013bGallardi et al, 2014). In this study we compared husbandry practices, at pilot commercial scale, for rope grown M. edulis before, during and after transport, in order to inform and improve the quality, quantity and efficiency.…”
Section: Introductionmentioning
confidence: 99%